Note, written by Éamonn Duggan from the Fr. Mathew Hall during the Easter Rising - Duggan, Éamonn, 1874-1936 (1916)
Duggan's note, dated 26 April, assures the recipient that he and his comrades are safe, but acknowledges that one of the men in this battalion has been injured. He also writes of a machine gun attack on their position, confirms it is no longer safe to receive visitors at the neighbouring convent and requests that word be sent to his fiancée May Duggan. The recipient of the note is unclear.
Duggan was a member of the Irish Volunteers and fought at the North Dublin Union and later Fr. Mathew Hall during the Easter Rising.
Keywords: Duggan, Éamonn, -- 1874-1936; Irish Volunteers